2021
DOI: 10.21873/invivo.12281
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of Immune-related Adverse Events in Patients With Advanced Gastric Cancer Treated With Nivolumab or Pembrolizumab: A Multicenter Retrospective Analysis

Abstract: Background: Immune-checkpoint inhibitors (ICI), including nivolumab and pembrolizumab, are among the standard treatments for previously treated advanced gastric cancer (AGC). This study aimed to evaluate the frequency of immune-related adverse events (irAEs) and the correlation between irAEs and their efficacy in AGC cases. Patients and Methods: Patients were divided into two groups according to irAE occurrence. The frequency of irAEs and the treatment outcome (response rate [RR], progression-free survival [PF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 23 publications
2
12
0
Order By: Relevance
“…13 Patients who had experienced AEs also survived longer in comparison to patients without AEs, as reported in a previous study. 14 Patients with TRAEs showed a mean OS time of 10.0 months in our cohort. Although the best response and AE were associated with the OS, as previously reported, they were not predictive factors because those factors were only obtained after the initiation of nivolumab treatment.…”
Section: Discussionmentioning
confidence: 62%
“…13 Patients who had experienced AEs also survived longer in comparison to patients without AEs, as reported in a previous study. 14 Patients with TRAEs showed a mean OS time of 10.0 months in our cohort. Although the best response and AE were associated with the OS, as previously reported, they were not predictive factors because those factors were only obtained after the initiation of nivolumab treatment.…”
Section: Discussionmentioning
confidence: 62%
“…IrAEs are pathologically characterized by macrophagic and lymphocytic infiltration into the normal tissues and result from the unintended effects of ICI-induced activation of the immune system. Since 2015, various studies have reported that irAEs are associated with a longer prognosis regardless of the treatment regimen [ 5 , 6 ]. Shimozaki et al reported that the development of multiple irAEs was associated with longer survivals than a single irAE [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…IrAEs have reportedly occurred in nearly all organs and are particularly common in non-cardiovascular organs such as the colon, lungs, endocrine glands, skin, and liver. Recently, several studies have reported that the development of irAEs was associated with clinical benefits for patients receiving ICI therapy [ 4 6 ]. Meanwhile, cancer and cardiovascular diseases often coexist because of shared risk factors such as hypertension, obesity, smoking, and diabetes [ 7 ], and multiple types of anti-cancer drugs and therapies can cause cardiovascular disorders.…”
Section: Introductionmentioning
confidence: 99%
“…The treatment with nivolumab may lead to immune-related adverse events (irAEs), which sometimes results in the interruption or discontinuation of the treatment [ 8 ]. Previous reports in melanoma, non-small-cell lung cancer, and gastric cancer patients have shown that the presence of irAEs with nivolumab were positively associated with their progression-free survival (PFS) and OS [ 9 13 ]. However, the correlation between irAEs and outcome of nivolumab for patients with MPM is still unknown.…”
Section: Introductionmentioning
confidence: 99%